Altered Metabolic Profile in Congenital Lung Lesions Revealed by 1H Nuclear Magnetic Resonance Spectroscopy. (29th January 2014) - Mimmi, Maria Chiara; Ballico, Maurizio; Nakib, Ghassan; Calcaterra, Valeria; Peiro, Jose Louis; Marotta, Mario; Pelizzo, Gloria
Abstract : Congenital lung lesions are highly complex with respect to pathogenesis and treatment. Large-scale analytical methods, like metabolomics, are now available to identify biomarkers of pathological phenotypes and to facilitate clinical management. Nuclear magnetic resonance (NMR) is a unique tool for translational research, as in vitro results can be potentially translated into in vivo magnetic resonance protocols. Three surgical biopsies, from congenital lung malformations, were analyzed in comparison with one control sample. Extracted hydrophilic metabolites were submitted to high resolution 1 H NMR spectroscopy and the relative concentration of 12 metabolites was estimated. In addition, two-dimensional NMR measurements were performed to complement the results obtained from standard monodimensional experiments. This is one of the first reports of in vitro metabolic profiling of congenital lung malformation. Preliminary data on a small set of samples highlights some altered metabolic ratios, dealing with the glucose conversion to lactate, to the relative concentration of phosphatidylcholine precursors, and to the presence of myoinositol. Interestingly some relations between congenital lung lesions and cancer metabolic alterations are found.